Serum c-Ski as a Novel Biomarker for Predicting Disease Progression and Prognosis via Regulating Inflammatory Response in Atrial Fibrillation - Yang, Xue; Han, Suxia; Wu, Jingjing (Journal of Medical Biochemistry, 2026)
Objective: Atrial fibrillation (AF) is an important risk factor for stroke, heart failure and death. The aim of this study is to investigate the relationship between serum c-Ski level and the progression of AF, as well as its regulatory mechanism on inflammatory response.Methods: A total of 164 patients with AF (55 paroxysmal, 55 persistent and 54 permanent) and 58 healthy controls from April 2023 to August 2024 were enrolled. The levels of c-Ski, IL-6 and TNF-α were detected by ELISA, and hs-CRP was detected by automatic biochemical analyzer. Left atrial volume index (LAVI) and left ventricular ejection fraction (LVEF) were measured by echocardiography. All patients were followed up for 4 times within 1 year. The recurrence of AF, cardiovascular events and all-cause mortality were recorded.Results: The patients with AF had a significantly higher serum c-Ski level than the control group (P19.00 ng/mL, sensitivity 71.95%, specificity 74.14%). c-Ski was positively correlated with IL-6, TNF-α and hs-CRP, negatively correlated with LVEF, and positively correlated with LAVI. After treatment, the level of c-Ski decreased (P17.57 ng/mL, sensitivity 78.13%, specificity 63.89%).Conclusions: Serum c-Ski level is closely related to the progression of AF, and its increase may accelerate atrial remodeling by activating inflammatory pathways. c-Ski can be used as a biomarker to predict AF recurrence and poor prognosis, and the established reference ranges and strict quality control procedures ensure the clinical applicability of c-Ski as a biomarker, providing a standardized basis for AF risk stratification and targeted therapy.
Keywords: Atrial fibrillation; c-Ski; Inflammatory cytokines; Prognosis; Biomarker